The Analysis Of Transformational Leadership Of Student Organization On Organizational Citizenship Behavior Through Person-Organization Fit And Emotional Intelligence As Mediation Variables - Putri, Anggie Rizqiyananda (Universitas Ciputra Surabaya, 2025)
This study investigates the influence of Transformational Leadership on Organizational Citizenship Behavior (OCB), with Person-Organization Fit (P-O Fit) and Emotional Intelligence (EI) as mediating variables. OCB reflects employees’ voluntary behaviors that contribute to organizational effectiveness beyond formal job requirements. Transformational Leadership is considered a key factor in shaping such behaviors. This research also examines how P-O Fit (as an external factor) and EI (as an internal factor) mediate the relationship between leadership and OCB. The study was conducted among student organization members from SU IBM and SU MEM at Ciputra University, involving 84 respondents. Data analysis was carried out using the Partial Least Squares (PLS) method via AMOS software. Findings indicate that Transformational Leadership does not directly influence OCB. However, it has a significant positive effect on both P-O Fit and EI. Among the mediators, only P-O Fit significantly affects OCB and partially mediates the relationship between Transformational Leadership and OCB. In contrast, EI does not show a significant mediating effect. These results emphasize the importance of value alignment between individuals and organizations in enhancing OCB, while suggesting that the role of Emotional Intelligence may be context-dependent and warrants further investigation.